THE EFFECTIVENESS OF MICROLEARNING TO IMPROVE LEARNERS' UNDERSTANDING IN LEARNING : LITERATURE REVIEW - Muhammad Rafeli Fakhlipi; Bachtiar Syaiful Bahri; Syaiputra Wahyuda Meisa Diningrat (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The digital era demands innovative solutions to attention fragmentation and information overload. This Literature Review (LR) aims to synthesize empirical evidence evaluating the effectiveness of Microlearning (ML) in improving Learner Comprehension. The method used involved screening 50 potential journals into 18 qualified scientific articles using strict criteria to eliminate non-cognitive studies. The synthesis confirms the superiority of ML, which is rooted in Cognitive Load Optimization. ML effectively reduces the Extrinsic Cognitive Load, thus maximizing the Germane Load for true schema construction. In addition, ML design encourages Active Engagement and retrieval practices, which significantly strengthen long-term knowledge retention. Consequently, ML is validated as an essential and adaptive pedagogical solution tailored to the cognitive profile of modern learners and is effective for Universal Learners.